Isolamento e caracterização de cepas de Saccharomyces cerevisiae de interesse em produção de vinho (Revista Brasileira de Ciências Farmacêuticas, 2006)
Despite the availability of several Saccharomyces cerevisiae commercial strains intended for wine production, strains isolated from winery regions are usually more adapted to their own climatic conditions, grapes and also partially responsible for particular characteristics that frequently identify specific wines and regions. Thus the microbiota of an important winery region (Colombo) was studied in order to isolate and characterize S. cerevisiae strains that could be used on wine production. From 61 yeasts isolated, 14 were identified as S. cerevisiae. Some of them showed fermentative characteristics even better than commercial strains indicating that they could be applied on wine production in order to increase the quality and assure the particular wine characteristics of that region.